Chromosome 3p allele loss in early invasive breast cancer: detailed mapping and association with clinicopathological features. Issue 5 (1st October 2001) - Martinez, A; Walker, R A; Shaw, J A; Dearing, S J; Maher, E R; Latif, F
Abstract : Aims —Chromosome 3p allele loss is a frequent event in many common sporadic cancers including lung, breast, kidney, ovarian, and head and neck cancer. To analyse the extent and frequency of 3p allelic losses in T1N0 and T1N1 invasive sporadic breast cancer, 19 microsatellite markers spread along 3p were analysed in 40 such breast carcinomas with known clinicopathological parameters. Methods —Loss of heterozygosity analysis was carried out using 3p microsatellite markers that were non-randomly distributed and chosen to represent regions that show hemizygous and/or homozygous losses in lung cancer (lung cancer tumour suppressor gene region 1 ( LCTSGR1) at 3p21.3 and LCTSGR2 at 3p12), and regions demonstrating suppression of tumorigenicity in breast, kidney, lung, and ovarian cancer. Results —Allelic loss was seen at one or more loci in 22 of these clinically early stage sporadic breast tumours, but none had complete 3p allele loss. Several regions with non-overlapping deletions were defined, namely: (1) 18 tumours showed loss at 3p21–22, a physical distance of 12 Mb; (2) 11 tumours showed loss at 3p12 within a physical distance of 1 Mb, this region is contained within LCTSGR2; (3) six tumours showed loss at 3p25–24, including the von Hippel-Lindau (VHL) locus; (4) five tumours showed loss at 3p14.2, including the fragile histidine triad (FHIT) locus. Conclusions —This is the largest study to date defining the extent and range of 3p allelic losses in early stage invasive breast cancer and the results indicate that region 3p21–22 containing LCTSGR1 and a region at 3p12 within LCTSGR2 are the most frequent sites of 3p allelic loss in these breast carcinomas. This suggests that tumour suppressor genes located in these regions may play important roles in the development of breast cancer. There was an association between increasing 3p allelic loss and increasing tumour grade and loss of progesterone (p = 0.0098) and oestrogen (p = 0.0472) receptor expression, indicating a link between 3p allelic loss and the regulation of differentiation.